Cu-[Ni, Co]-Si-based copper alloy sheet material, energizing member, and heat dissipation member
By controlling the content of S and the number density of S-phase-containing particles in the Cu-[Ni,Co]-Si-based copper alloy, combined with multiple cold rolling and heat treatment processes, the problem of decreasing bending processability caused by S addition is solved, and the balance between stamping and bending processability is achieved, and the fatigue characteristics and conductivity are adjusted to a medium strength level, and the fatigue characteristics and conductivity are improved.
Patent Information
- Application Number
- CN202410081193.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-01-19
- Publication Date
- 2025-03-28
AI Technical Summary
When the prior art is added to improve the stamping properties of Cu-[Ni,Co]-Si-based copper alloys by S, the bending processability is easily reduced, and the higher strength increases the manufacturing load, resulting in an increase in manufacturing cost.
By controlling the S content and the number density of S-phase-containing particles in the Cu-[Ni,Co]-Si-based copper alloy, the chemical composition and structure of the sheet material with a length diameter of 2.0 μm or more and less than 5.0 μm are ensured to be 50/mm2 or more, and the number density of S-phase-containing particles with a length diameter of 5.0 μm or more is 50/mm2 or less. The chemical composition and structure of the sheet material are adjusted in combination with multiple cold rolling and heat treatment processes.
It is achieved while maintaining good bending processability and significantly improving stamping properties, and adjusting to a medium strength level (the tensile strength in the rolling direction is above 500MPa and less than 900MPa), which improves fatigue characteristics and conductivity, and reduces manufacturing load and manufacturing cost.
Smart Images

Figure CN119710357A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a Cu-[Ni, Co]-Si copper alloy sheet material having improved stamping properties and bending properties, and a current-carrying component and a heat-dissipating component using the Cu-[Ni, Co]-Si copper alloy sheet material as a material. The Cu-[Ni, Co]-Si copper alloy is a general term for Cu-Ni-Si copper alloy, Cu-Co-Si copper alloy, and Cu-Ni-Co-Si copper alloy. Background Art
[0002] Cu-[Ni, Co]-Si copper alloys have a good balance between strength and conductivity among copper alloys and can be used for current-carrying parts such as connectors and lead frames, heat dissipation parts of electronic devices, etc. When processing copper alloy sheets into current-carrying parts or heat dissipation parts, they are generally processed by stamping and bending. So far, various studies have been conducted on methods to improve the stamping and bending properties of Cu-[Ni, Co]-Si copper alloys.
[0003] Patent Document 1 discloses a technique for improving strength and bending workability by rationalizing the structure of a Cu-[Ni, Co]-Si copper alloy. The document does not show a material to which S is added, and does not particularly teach improvement in stampability.
[0004] Patent Document 2 discloses a technique for improving stamping properties by making the number density of precipitates near the surface of a plate greater than that of the central portion in a Cu-[Ni, Co]-Si copper alloy. In this document, a case where there are few collapsed edges and burrs on the cut surface is evaluated as good stamping properties (paragraph 0091). No material to which S is added is shown.
[0005] Patent Document 3 discloses a technique for improving strength and bendability by controlling the cooling rate of a solution treatment in a Cu-[Ni, Co]-Si copper alloy. No S-added material is shown, and there is no particular teaching on improvement of stampability.
[0006] Patent Document 4 discloses a technique for improving solder wettability and spring properties by optimizing the size and number density of precipitates in a Cu-[Ni, Co]-Si copper alloy by performing a three-stage aging treatment process. No S-added material is shown, and there is no special teaching on improving stamping properties and bending properties.
[0007] Patent Document 5 discloses a technique for improving strength and punchability by adding S to a Cu-[Ni, Co]-Si copper alloy and controlling the number density of Mg-S particles. There is no particular teaching on improving bending workability.
[0008] Patent Document 6 discloses a technique for improving bending workability and stress relaxation properties by optimizing the grain size and softening degree before and after pre-annealing in a Cu-[Ni, Co]-Si copper alloy. No S-added material is shown, and there is no special teaching on improving stamping properties.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2011-117034
[0012] Patent Document 2: Japanese Patent Application Publication No. 2012-224922
[0013] Patent Document 3: Japanese Patent Application Publication No. 2015-187308
[0014] Patent Document 4: Japanese Patent Application Publication No. 2011-214088
[0015] Patent Document 5: Japanese Patent Application Publication No. 2021-134376
[0016] Patent Document 6: Japanese Patent Application Publication No. 2013-95977 Summary of the invention
[0017] Problems to be solved by the invention
[0018] Recently, the miniaturization, narrow pitch, and mass production of components are developing continuously, and the importance of suppressing the wear of molds used in bending processes, etc. is increasing. According to the technology of patent document 5, by making a microstructure state (metallographic state) in which Mg-S inclusions are dispersed in Cu-[Ni, Co]-Si copper alloys, it is possible to achieve high strength and significant improvement in punchability. That is, it is shown that the addition of S is extremely effective in improving punchability. However, if the punchability is improved by adding S, the bending workability is sometimes reduced, and further improvement is desired. In addition, in the technology of patent document 5, the strength level becomes very high, but there are also many uses such as current-carrying parts and heat dissipation parts that do not require such high strength. Excessive high strength increases the manufacturing load of parts, which becomes the main reason for the lack of a proper balance between the required properties and manufacturing costs.
[0019] The object of the present invention is to provide a technology for improving stamping properties while maintaining good bending workability by using a method of adding S to a Cu-[Ni, Co]-Si copper alloy, which technology can obtain a plate with a medium strength level (tensile strength in the rolling direction of 500 MPa or more and less than 900 MPa) with high versatility.
[0020] Means for solving problems
[0021] In order to achieve the above-mentioned object, the following invention is disclosed in this specification.
[0022] [1] A copper alloy sheet having the following chemical composition, which comprises, expressed in mass %, a total of Ni and Co of 1.00 to 3.60%, Si: 0.20 to 2.00%, S: 0.005 to 0.10%, Ag: 0 to 1.00%, Al: 0 to 3.00%, B: 0 to 0.50%, Cr: 0 to 1.00%, Fe: 0 to 3.00%, Mg: 0 to 1.50%, Mn: 0 to 1.50%, P: 0 to 0.50%, Sn: 0 to 3.00%, Ti: 0 to 1.00%, Zn: 0 to 3.00%, Zr: 0 to 1.00%, and the remainder being Cu and unavoidable impurities, wherein the number density of S-containing particles having a major diameter of 2.0 μm or more and less than 5.0 μm is 50 particles / mm 2 The number density of S-containing particles with a major diameter of 5.0 μm or more is 50 particles / mm 2 the following.
[0023] [2] The copper alloy sheet material according to [1] above, wherein the total content of Ag, Al, B, Cr, Fe, Mg, Mn, P, Sn, Ti, Zn and Zr is 4.00 mass % or less.
[0024] [3] The copper alloy sheet material according to [1] or [2] above, wherein the Ni content is 0.80 to 3.50 mass %.
[0025] [4] The copper alloy sheet material according to any one of [1] to [3] above, wherein the tensile strength in the rolling direction is 500 MPa or more and less than 900 MPa.
[0026] [5] The copper alloy sheet material according to any one of [1] to [4] above, wherein the electrical conductivity is 40% IACS or higher.
[0027] [6] A copper alloy sheet material according to any one of [1] to [5] above, wherein the ratio MBR / t of the minimum bending radius MBR without cracking in a 90° W bending test under BW according to the technical standard of Japan Copper Alloy Association JCBA T307:2007 to the sheet thickness t is 2.5 or less.
[0028] [7] The copper alloy sheet material according to any one of [1] to [6] above, wherein in a bidirectional vibration fatigue test using a cantilever resonance method using a test piece with the longitudinal direction being a perpendicular direction to the rolling, the fatigue limit under a load stress of 300 MPa is 10 6 Loop above.
[0029] [8] The method for producing a copper alloy sheet material according to any one of [1] to [7] above, comprising:
[0030] A casting step, wherein a copper alloy melt having a temperature of 1180 to 1420° C. and having the chemical composition according to the above [1] is poured into a mold, solidified, and then cooled at an average cooling rate of 65° C. / s or more from 1100° C. to 600° C. to obtain a cast piece;
[0031] A hot rolling step, wherein the cast sheet is heated to 880-1100° C. and then hot rolled at a total rolling rate of 85% or more to obtain a hot rolled sheet;
[0032] A first intermediate cold rolling step, wherein the hot-rolled sheet is subjected to cold rolling with a total rolling ratio of 60% or more;
[0033] An intermediate annealing step, wherein the sheet obtained in the first intermediate cold rolling step is subjected to a heat treatment at 430 to 620° C. for 0.1 to 20 hours;
[0034] A final intermediate cold rolling step, wherein the plate obtained in the intermediate annealing step is subjected to cold rolling with a total rolling ratio of 75% or more;
[0035] A solution treatment step, wherein the plate obtained in the final intermediate cold rolling step is subjected to a heat treatment at 800 to 1020° C. for 10 to 600 seconds;
[0036] An aging treatment step, wherein the plate obtained in the solution treatment step is subjected to a heat treatment at 400 to 550° C. for 1 to 24 hours;
[0037] a finishing cold rolling step, wherein the plate obtained in the aging treatment step is subjected to cold rolling with a total rolling ratio of 10 to 80%; and
[0038] The finishing heat treatment step includes subjecting the sheet obtained in the finishing cold rolling step to a heat treatment at 140 to 500° C. for 5 to 3600 seconds.
[0039] [9] According to the method for manufacturing a copper alloy sheet material described in [8] above, in the chemical composition of the copper alloy melt injected into the mold in the casting step, the total content of Ag, Al, B, Cr, Fe, Mg, Mn, P, Sn, Ti, Zn and Zr is less than 4.00 mass%.
[0040]
[10] The method for producing a copper alloy sheet material according to [8] or [9] above, wherein the chemical composition of the copper alloy melt poured into the mold in the casting step contains 0.80 to 3.50 mass % Ni.
[0041]
[11] A current-carrying component using the copper alloy sheet material according to any one of [1] to [7] as a material.
[0042]
[12] A heat dissipation component using the copper alloy sheet material according to any one of [1] to [7] as a material.
[0043] In this specification, "plate material" means a sheet-like metal material. Thin sheet-like metal materials are sometimes also called "foils", and such "foils" are also included in the "plate material" mentioned here. Sheet-like metal materials that are wound into long strips in a coil shape are also included in the "plate material". In addition, in this specification, the thickness of the sheet-like metal material is referred to as the "plate thickness". In addition, the so-called "plate surface" means the surface perpendicular to the plate thickness direction of the plate. The plate surface is sometimes also called the "rolled surface".
[0044] In this specification, the notation “n1 to n2” indicating a numerical range means “n1 or more and n2 or less.” Here, n1 and n2 are numerical values satisfying n1<n2.
[0045] In this specification, "punching property" is an indicator evaluated by the area ratio of the "shear surface" in the cut surface (cut) when punching is performed with a die with an appropriate gap (interval). In order to stabilize the quality in the punching process, it is important to extend the life of the die. In the cut surface of the metal plate formed by punching, the shear surface and the fracture surface are usually formed (see Figure 1 ). When punching is performed with an appropriate gap, the material with a smaller proportion of the shear surface is more beneficial to the extension of the die life. Therefore, in this specification, when punching is performed under the same conditions, the material with a smaller proportion of the shear surface in the cut surface is considered to have better punchability.
[0046] The “major diameter” is the maximum value that the length of a line segment connecting two points on the contour line of the particle located on the image plane (limited to the line segment not existing outside the particle) can take.
[0047] The total rolling reduction (%) in a certain rolling process is determined by the following formula (1).
[0048] Total rolling rate (%) = 100 × (h0-h1) / h0…(1)
[0049] h0: Plate thickness before the first rolling pass in the rolling process (mm)
[0050] h1: Plate thickness at the end of the final rolling pass of the rolling process (mm)
[0051] Effects of the Invention
[0052] According to the present invention, a Cu-[Ni, Co]-Si copper alloy sheet material having a medium strength level and high versatility and having improved punchability while ensuring good bending workability can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 The figure schematically shows the shape of the cutout of the metal plate after punching. DETAILED DESCRIPTION
[0054] [Chemical composition]
[0055] In the following, "%" regarding the composition of components means "mass %" unless otherwise specified.
[0056] In the present invention, the Cu (copper) - [Ni, Co] - Si copper alloy containing at least one of Ni (nickel) and Co (cobalt) and Si (silicon) is the object. Ni, Co and Si form precipitates mainly composed of (Ni, Co) 2Si, which contribute to the improvement of strength and conductivity. It also contributes to the improvement of fatigue properties. The total content of Ni and Co can be set in the range of 1.00 to 3.60%, and the Si content can be set in the range of 0.20 to 2.00%. In this range, the appropriate strength level described later can be obtained. It is more preferable to contain Ni in the range of 0.80 to 3.50%.
[0057] S (sulfur) is an important component element in the present invention. Generally, in copper alloys, S is mostly treated as an impurity from the viewpoint of suppressing the deterioration of hot workability and the reduction of material properties. In the manufacturing process of copper alloys, the S content is usually reduced by methods such as degreasing of raw materials and flotation separation in the melt. However, in the present invention, the stamping performance is improved by dispersing S-containing phase particles in the material. Therefore, as a generation source of S-containing phase particles, a prescribed amount of S is contained in the copper alloy. As a result of various studies, it is effective to control the S content within the range of S: 0.005 to 0.10%. If the S content is too small, the amount of S-containing phase particles generated becomes insufficient, and the stamping performance improvement effect cannot be obtained. It is more preferable to make the S content 0.006% or more, and more preferably 0.008% or more. If the S content becomes excessive, the hot workability deteriorates and cracks are easily generated during hot rolling. In addition, from the viewpoint of obtaining good bending workability, a low S content is effective. The S content is preferably adjusted to be within the range of 0.05% or less, and more preferably 0.03% or less.
[0058] As other optional elements, Ag (silver), Al (aluminum), B (boron), Cr (chromium), Fe (iron), Mg (magnesium), Mn (manganese), P (phosphorus), Sn (tin), Ti (titanium), Zn (zinc), Zr (zirconium) can be contained as needed. The content of these optional elements can be set in the range of Ag: 0-1.00%, Al: 0-3.00%, B: 0-0.50%, Cr: 0-1.00%, Fe: 0-3.00%, Mg: 0-1.50%, Mn: 0-1.50%, P: 0-0.50%, Sn: 0-3.00%, Ti: 0-1.00%, Zn: 0-3.00%, Zr: 0-1.00%. From the viewpoint of good balance of stamping property, bending workability, strength, and fatigue properties, the total content of these optional elements is preferably 4.00% by mass or less.
[0059] If economic efficiency and manufacturability are taken into consideration, the content of the above optional elements is more preferably in the range of Ag: 0-0.40%, Al: 0-2.00%, B: 0-0.20%, Cr: 0-0.70%, Fe: 0-2.00%, Mg: 0-1.20%, Mn: 0-1.20%, P: 0-0.20%, Sn: 0-2.00%, Ti: 0-0.80%, Zn: 0-2.00%, and Zr: 0-0.40%. In this case, the total content of these elements is more preferably 2.50 mass % or less.
[0060] In addition, the content of the above optional elements can be controlled within the range of Ag: 0-0.20%, Al: 0-1.00%, B: 0-0.10%, Cr: 0-0.30%, Fe: 0-1.00%, Mg: 0-0.60%, Mn: 0-0.60%, P: 0-0.10%, Sn: 0-1.00%, Ti: 0-0.40%, Zn: 0-1.00%, Zr: 0-0.20%. In this case, the total content of these elements can be controlled to be 1.20% by mass or less.
[0061] For elements other than the above, it is allowed to contain elements other than the above within the range that does not hinder the purpose of the present invention (improving stamping properties while maintaining good bending workability). Specifically, the total content of elements other than Ni, Co, Si, S, Ag, Al, B, Cr, Fe, Mg, Mn, P, Sn, Ti, Zn, Zr, and Cu (hereinafter sometimes referred to as "non-specified elements") is preferably 0.50% or less, and can be managed to be less than 0.10%. The content of non-specified elements can be grasped by, for example, quantifying substantially all elements that can be contained in the copper alloy plate using the following analysis method.
[0062] (Example of quantitative method for alloy elements)
[0063] O (oxygen) and N (nitrogen) are quantified using an oxygen, nitrogen, and hydrogen analyzer (e.g., ONH-836 manufactured by LECO), H (hydrogen) is quantified using a hydrogen analyzer (e.g., EMGA-921 manufactured by Horiba, Ltd.), C (carbon) and S (sulfur) are quantified using a carbon-sulfur analyzer (e.g., CS844 manufactured by LECO), elements of the 2nd to 6th periods (excluding C, N, O, Group 17 elements, Group 18 elements, Tc (technetium), Po (polonium), and Pm (promethium)) are quantified using ICP-MS (e.g., 7900 manufactured by Agilent), and F (fluorine), Cl (chlorine), and Br (bromine) are quantified using a combustion-ion chromatograph (e.g., DIONEX ICS-1600 manufactured by Thermo Scientific).
[0064] Regarding the chemical composition of the copper alloy sheet material according to the present invention, in addition to being limited to "consisting of one or more of Ni and Co, Si, S, the above-mentioned optional elements (including the case where the total is 0 mass%), the balance Cu and inevitable impurities", it can also be limited to "consisting of one or more of Ni and Co, Si, S, the above-mentioned optional elements (including the case where the total is 0 mass%), the above-mentioned unspecified elements (including the case where the total is 0%), and the balance Cu".
[0065] [Contains S phase particles]
[0066] In this specification, the "S-containing phase particles" are particles in which the presence of S can be observed by EDX (energy dispersive X-ray fluorescence analysis) among the second phase particles present in the copper alloy. These particles include particles of S alone and compound particles containing S. It is believed that compounds mainly composed of sulfides of metals that are easily bonded to S, such as MgS, MnS, and CrS, are formed depending on the alloying elements contained as the compound particles.
[0067] According to the research of the inventors, it is known that the S-containing particles with a particle size of 2.0 μm or more and less than 5.0 μm based on the major diameter observed in the observation of the sample surface parallel to the plate surface are extremely effective for improving the punchability. It is believed that the S-containing particles with a major diameter of 2.0 μm or more and less than 5.0 μm become the starting point of fracture during punching, which is believed to help reduce the proportion of the shear surface. On the other hand, the coarse S-containing particles with a particle size of 5.0 μm or more in the major diameter become the main reason for reducing bending workability and fatigue characteristics. Such coarse S particles are easy to become the starting point of cracks during bending.
[0068] As a result of detailed studies, it was found that by setting the number density of S-containing particles with a major diameter of 2.0 μm or more and less than 5.0 μm to 50 particles / mm 2As a result, the proportion of the shear surface in the cut formed when the shearing process (stamping) is performed with an appropriate gap is significantly reduced. As a result, the life of the die is extended, so the disadvantages of the punching die are reduced in mass production, and the quality of the parts is stable. That is, the punchability is significantly improved. It is difficult to make the number density of S-containing particles with a long diameter of more than 2.0μm and less than 5.0μm very large. The number density of the S-containing particles is usually 1500 / mm 2 Below, can be 70~1200 pieces / mm 2 On the other hand, by controlling the number density of S-phase particles with a major diameter of 5.0 μm or more to 50 particles / mm 2 Hereinafter, good bending workability is ensured and fatigue properties are also improved. Such a structural state can be achieved by following the above-mentioned chemical composition and the manufacturing method described below.
[0069] (Method for measuring the number density of particles containing S phase)
[0070] The plate surface of the copper alloy plate is ground to obtain a sample surface for EDX measurement. The sample surface is observed using a FE-SEM (field emission scanning electron microscope) equipped with an EDX device, and a measurement area of 300μm×400μm in size is randomly determined. In the FE-SEM observation, JSM-7200F manufactured by JEOL Ltd. is used to obtain secondary electron images under the conditions of an acceleration voltage of 15kV, a current of 13A, and a WD (working distance) of 10mm. For the secondary electron image, EDX point analysis is performed on particles with a major diameter of more than 1μm to determine whether these particles are S-containing particles. In addition, the so-called major diameter is the length of the longest line segment that can be drawn in the particle (limited to the line segment that does not run out of the outline of the particle). In the above-mentioned EDX point analysis, particles with an analytical concentration of S of more than 0.5% by mass are treated as S-containing particles. For the secondary electron image obtained, count the number of S-containing particles with a long diameter of 2.0 μm or more and less than 5.0 μm, and the number of S-containing particles with a long diameter of 5.0 μm or more existing in the measurement area. For particles whose part is cut by the boundary of the measurement area, the boundary portion is regarded as a part of the outline of the particle, and the long diameter is measured using the particle portion located in the measurement area. This operation is performed for multiple non-repeating measurement areas, and the total number of S-containing particles with a long diameter of 2.0 μm or more and less than 5.0 μm and the total number of S-containing particles with a long diameter of 5.0 μm or more are respectively divided by the total area of the measurement area (mm 2 ), and thus calculate the number density (pieces / mm 2). The number density calculation operation is performed for three or more non-repeating measurement areas. For the values of the number density of S-containing particles with a long diameter of 2.0 μm or more and less than 5.0 μm obtained in each measurement area, the arithmetic mean is calculated and adopted as the number density of S-containing particles with a long diameter of 2.0 μm or more and less than 5.0 μm in the plate. Similarly, for the values of the number density of S-containing particles with a long diameter of 5.0 μm or more obtained in each measurement area, the arithmetic mean is calculated and adopted as the number density of S-containing particles with a long diameter of 5.0 μm or more in the plate. Furthermore, the measurement of the long diameter of each S-containing particle and the counting of the number of particles can be performed using image processing software (such as ImageJ).
[0071] [Tensile strength and electrical conductivity]
[0072] The required strength level of copper alloy sheets used in electrical parts such as connectors, heat dissipation parts of electronic devices, etc. varies depending on the application, and excessive high strength becomes the main reason for increasing the manufacturing load of the parts and causing an increase in manufacturing costs. In the invention of Patent Document 5 that uses Mg-S particles to improve stamping properties, high-strength sheets with a tensile strength of 900 MPa or more in the rolling direction are targeted. The present invention can also improve the stamping properties of Cu-[Ni, Co]-Si copper alloy sheets with a medium strength level of tensile strength in the rolling direction of, for example, 500 MPa or more and less than 900 MPa, and also ensure good bending workability. In addition, a conductivity of 40% IACS or more is obtained at the same time. The conductivity of the copper alloy sheet according to the present invention is usually in the range of 70% IACS or less.
[0073] Ni, Co and Si improve the strength of the copper alloy sheet by forming precipitates. Mg and S are also the main reasons for increasing the strength of the copper alloy sheet by forming Mg-S particles. In addition, in the method for manufacturing the copper alloy sheet of the present invention described later, the amount of precipitates generated can be adjusted by the time of aging treatment, and the strength of the final sheet can be adjusted by the total rolling rate of the finish cold rolling. In the present invention, by appropriately combining these element technologies that affect the strength, while fully ensuring the number density of S-containing particles with a long diameter of 2.0 μm or more and less than 5.0 μm, a medium strength level of 500 MPa or more and less than 900 MPa is achieved.
[0074] [Bending properties]
[0075] When processing into current-carrying parts, etc., bending is often involved. Considering the use of Cu-[Ni, Co]-Si copper alloy sheets, in order to obtain high reliability when processing into current-carrying parts and heat dissipation parts, it is desired to have a bending processability in which the ratio of the minimum bending radius MBR and the plate thickness t without cracking according to the W bending test under BW in accordance with the technical standard of the Japan Copper Draw Association JCBA T307:2007 is 2.5 or less. It is more preferred that the MBR / t under BW is less than 2.0, and further preferably less than 1.5. It is also possible to obtain a bending processing type in which the MBR / t under BW is 0.0 (no cracks are generated in close bending). BW (Bad Way) means that the bending axis becomes parallel to the rolling direction.
[0076] It should be noted that JCBA T307:2007 states that "This standard applies to the evaluation of the bending workability of copper and copper alloy thin strips with a thickness of 0.1 mm or more and 0.8 mm or less." According to the research of the present inventors, it has been confirmed that the W bending test of the method described in the standard can be used to evaluate the bending workability of Cu-[Ni, Co]-Si copper alloy sheets with a thickness of less than 0.1 mm. Therefore, in the present invention, the W bending test method under BW shown in JCBA T307:2007 is also expanded to the case where the thickness is less than 0.1 mm (for example, 0.02 mm or more and less than 0.1 mm), and is directly applied.
[0077] [Fatigue properties]
[0078] For current-carrying parts such as connectors, stress is sometimes repeatedly applied, so the use of plates with good fatigue properties becomes advantageous for improving the reliability of the parts. For Cu-[Ni, Co]-Si copper alloy plates in which S-phase particles are dispersed, it is known that good fatigue properties can be obtained by adjusting the total content of Ni and Co and the Si content to the above-mentioned appropriate range, and by controlling the number density of coarse S-phase particles to a low level after fully exerting precipitation strengthening. Considering the use of Cu-[Ni, Co]-Si copper alloy plates, in a bidirectional vibration fatigue test using a cantilever resonance method using a test piece with the longitudinal direction being the rolling right angle direction (TD), the fatigue limit under a load stress of 300 MPa is preferably 1.0×10 6 Cycles (millions of cycles) or more. "Fatigue" can be determined by detecting a decrease in the resonance frequency associated with a decrease in the Young's modulus.
[0079] [Manufacturing method]
[0080] The copper alloy sheet material described above can be produced, for example, by the following production process.
[0081] Casting → hot rolling → first intermediate cold rolling → intermediate annealing → final intermediate cold rolling → solution treatment → aging treatment → finishing cold rolling → finishing heat treatment
[0082] Although not described in the above steps, face grinding is performed as needed after hot working, and pickling, grinding, or degreasing is performed as needed after each heat treatment.
[0083] [Casting]
[0084] The copper alloy melt at 1180-1420°C having the above chemical composition is poured into a casting mold for casting. It is preferred to keep the copper alloy melt in the above temperature range for, for example, about 2 to 8 hours before casting. If the melt temperature before casting is lower than 1180°C, a large amount of coarse S-containing phase (S single phase, S compound) is easily generated in the cast sheet, which becomes the main reason for reducing bending workability and fatigue properties. For the homogenization of the melt, it is beneficial to increase the melt temperature before casting. If the temperature is too high, it becomes uneconomical, so it is preferably in the range of 1420°C or less. As a casting method, general methods such as continuous casting, semi-continuous casting, and agglomeration can be applied. In the present invention, the control of the cooling rate is very important. Specifically, the copper alloy melt at the above temperature is injected into the casting mold, and after solidification, it is cooled under the condition that the average cooling rate from 1100°C to 600°C becomes 65°C / s or more. Therefore, a casting equipment with sufficient cooling capacity is used. If the average cooling rate from 1100°C to 600°C is lower than 65°C / s, a large amount of coarse S-containing phase is easily generated in the obtained cast piece, which becomes the main reason for reducing the bending workability and fatigue properties. In addition, excessively increasing the cooling rate increases the burden on the equipment and becomes uneconomical. The average cooling rate from 1100°C to 600°C is preferably adjusted in a range of, for example, 230°C / s or less.
[0085] In the smelting of copper alloys, S is generally treated as an impurity, and the raw materials and refining methods are usually managed in a manner to minimize its content. In the present invention, however, it is necessary to strictly control the S content in a manner such that the S content within the above-mentioned specified content range enters the copper alloy. For the addition of S, for example, a pre-prepared Cu-S master alloy can be used.
[0086] [Hot rolling]
[0087] After the slab is heated to 880-1100°C, the slab is subjected to hot rolling with a total rolling reduction of 85% or more to obtain a hot-rolled plate. From the viewpoint of promoting the homogenization of the structure (metallographic structure), it is more preferable to make the heating temperature of the slab 950-1100°C. The heating holding time of the slab is preferably set in the range of 0.5-12 hours. In order to obtain the desired metallographic structure containing the dispersed S-phase particles, it is effective to separate the coarse S-containing phase in the hot rolling process. Therefore, the total rolling reduction in hot rolling is set to 85% or more. The upper limit of the total rolling rate for hot rolling can be set according to the capacity of the hot rolling mill. Usually, it can be set in the range of less than 95%.
[0088] [First intermediate cold rolling, intermediate annealing, final intermediate cold rolling]
[0089] In the present invention, a plurality of cold rolling steps with intermediate annealing are performed before solution treatment. The first cold rolling after hot rolling is called "first intermediate cold rolling", and the last cold rolling before solution treatment is called "final intermediate cold rolling".
[0090] The total rolling reduction of the first intermediate cold rolling is preferably 60% or more. For the final intermediate cold rolling, in order to introduce deformation (strain) that promotes recrystallization in the subsequent solution treatment, the total rolling reduction is preferably 75% or more. For all these cold rolling steps, the upper limit of the total rolling reduction can be set according to the capacity of the rolling mill. It can usually be set within a range below 99%.
[0091] The intermediate annealing between the first intermediate cold rolling and the final intermediate cold rolling is carried out at 430-620°C for 0.1-20 hours. If the temperature is too low or the holding time is too short, the deformation may not be removed enough and cracks may occur during the subsequent cold rolling. If the temperature is too high or the holding time is too long, the material strength may decrease.
[0092] If necessary, one or more intermediate cold rolling and intermediate annealing steps may be further inserted between the intermediate annealing and the final intermediate cold rolling. In this case, the inserted intermediate annealing may be performed under the same conditions as the intermediate treatment, and the inserted intermediate cold rolling may be performed under the same conditions as the first intermediate cold rolling.
[0093] [Solution treatment, aging treatment]
[0094] Next, a solution treatment is performed at 800 to 1020° C. for 10 to 600 seconds, and then an aging treatment is performed at 400 to 550° C. for 1 to 24 hours.
[0095] [Fine cold rolling, fine heat treatment]
[0096] After aging treatment, finish cold rolling is performed under the condition of a total rolling rate of 10 to 80%. Then, a finish heat treatment is performed for the purpose of reducing residual stress, improving bending workability, and improving stress relaxation resistance due to the reduction of pores and dislocations on the sliding surface. The conditions for the finish heat treatment can be heating conditions that do not cause recrystallization within the range of a holding temperature of 140 to 500°C and a holding time of 5 to 3600 seconds. The final plate thickness can be, for example, in the range of 0.02 to 0.40 mm.
[0097] [Electrical parts and heat dissipation parts]
[0098] The Cu-[Ni, Co]-Si copper alloy sheet obtained as described above has excellent stamping properties and good bending properties, and can be adjusted to a medium strength level (medium strength level), so it can be processed into current-carrying parts such as connectors and heat dissipation parts of electronic devices by using a process that improves the life of the die and avoids excessive manufacturing loads to suppress manufacturing costs. In addition, the fatigue properties of the obtained parts are also good.
[0099] Example
[0100] The copper alloy with the chemical composition shown in Tables 1 to 4 was melted and cast using a vertical semi-continuous casting machine. The gas phase space that the molten metal contacts during casting is the atmospheric atmosphere. For the addition of S, a Cu-20.1 mass% S alloy was used. The molten metal temperature before casting and the molten metal holding time at this temperature are shown in Tables 1 to 4. A thermocouple is arranged in the mold, and a thermocouple is introduced into the inside of the solidified casting after the molten metal is injected to monitor the temperature of the casting during cooling, and the average cooling rate from 1100°C to 600°C is calculated. The cooling rate of the casting is controlled by the amount of water used to cool the mold and the amount of water used to cool the casting coming out of the mold.
[0101] In addition, the analysis samples collected from the cast pieces were analyzed for the elements listed in Tables 1 to 4 by the method described in the above-mentioned "Example of the quantitative method of alloying elements".
[0102] After the obtained castings were kept at the temperature shown in Tables 1 to 4 for 1 to 10 hours, they were taken out of the furnace and hot rolled with the total rolling ratio shown in Tables 1 to 4. After hot rolling, the oxide layer on the surface was removed by mechanical grinding (face grinding). Then, excluding some examples (No. 51, 54), the first intermediate cold rolling, intermediate annealing, final intermediate cold rolling, solution treatment, aging treatment, finish cold rolling, and finish heat treatment were sequentially carried out under the conditions shown in Tables 1 to 4. In No. 51 and 54, intermediate annealing and final intermediate cold rolling were omitted. In addition, the values of the total rolling ratio (%) in each rolling process recorded in the table are rounded off after the decimal point.
[0103] In each example, a plate obtained by the finish heat treatment was used as a test material and subjected to the following examination. The plate thickness of the test material was 0.2 mm in each example.
[0104] (Contains the number density of S phase particles)
[0105] According to the above-mentioned "method for measuring the number density of S-phase particles", the test surface parallel to the plate surface of the test material was observed using a FE-SEM (JSM-7200F manufactured by JEOL Ltd.) equipped with an EDX device, and the S-phase particles were confirmed by EDX analysis and secondary electron images were taken. The sample surface was prepared by electrolytic grinding after mechanical grinding using grinding paper with grinding stone serial number #1000. The electrolytic grinding was carried out at 15V for 20 seconds. One measurement area was set as a rectangular area of 300μm×400μm, and measurements were performed on 3 non-overlapping measurement areas. The total area of the measurement area is 0.36mm 2 The measurement of the major diameter of the S-phase-containing particles and the counting of the number of particles whose major diameters were within a predetermined range were performed by the following method using the image analysis software ImageJ (National Institutes of Health (NIH), Version 1.52a).
[0106] First, in the above-mentioned secondary electron images, the particles that are determined not to contain S-phase particles are painted black. Then, in terms of the analysis conditions of the above-mentioned software, in the "Set Scale" screen that is displayed by selecting Analyze and Set Scale in sequence, the number of pixels of the scale length of the photographed FE-SEM image is measured and the Distance in pixels is input. Next, the length of the scale (μm) is input as the Known distance, the Pixel aspect ratio is set to 1.0, and the Unit of length is set to μm, and the size of the precipitate can be confirmed on the software. Then, in the "Resize ImageCanvas" screen, the Width is set to 1280 pixels, the Height is set to 950 pixels, and the Position is set to Top-Center to display the image of the FE-SEM image portion that does not include the scale portion. After setting the scale and deleting the scale display, select Image, Adjust, and Threshold in sequence to display the "Threshold" screen. In this way, the brightness of all pixels is reversed so that the pixel with the lowest brightness becomes 255 and the pixel with the highest brightness becomes 0. The threshold is set to the value that is closest to 5% of the number of pixels below this value relative to the total number of pixels. The part where the precipitate particles exist is binarized and identified. Then, in the "Analyze Particles" screen of the same software, a separate precipitate area with an area of less than 0.1 μm is selected. 2 In order to remove the condition of the situation, set Size to "0.10-Infinity". Furthermore, set Circularity to 0.00-1.00, set the Fit Ellipse item to be checked in the "Set Measurements" screen, perform particle analysis, and find the number of S-containing particles with a major diameter (expressed by the Major item name) of 2.0μm or more and less than 5.0μm and the number of S-containing particles with a major diameter of 5.0μm or more in the field of view.
[0107] (Electrical conductivity)
[0108] The electrical conductivity of each test material was measured using the double bridge average cross-sectional area method in accordance with JIS H0505. Considering the electrical conductivity required for current-carrying parts such as small connectors, a conductivity of 40% IACS or more was considered acceptable.
[0109] (Tensile Strength)
[0110] Tensile test pieces (JIS No. 5) in the rolling direction were sampled from each test material, and the tensile test was carried out in accordance with JIS Z2241 with the test number n = 3 to measure the tensile strength. The average value of n = 3 was taken as the result value of the test material. From the viewpoint of ensuring bending workability and high reliability in electrical parts such as connectors, the tensile strength in the rolling direction was judged to be 500 MPa or more and less than 900 MPa as qualified.
[0111] (Bending properties)
[0112] The ratio of the minimum bending radius MBR to the plate thickness t, MBR / t, which does not cause cracks in the W bending test under BW according to the technical standard of the Japan Copper Draw Association JCBA T307:2007, was calculated. The size of the test piece was set to 30 mm in the length at right angles to the rolling on the plate surface and 10 mm in the length in the rolling direction (width of the test piece). The determination of the presence or absence of cracks on the surface of the bent portion was carried out in accordance with JCBAT307:2007. In the appearance observation of the bent portion surface, for samples judged as "wrinkles: large", for the part with the deepest wrinkles, a specimen cut perpendicularly to the bending axis direction was made, and its polished cross section was observed with an optical microscope to confirm whether cracks that developed into the inside of the plate thickness had occurred. If such cracks did not occur, it was judged as "no cracks were found". Considering the use of the material of the present invention, an MBR / t of 2.5 or less according to this test is judged to be qualified.
[0113] (Punchability)
[0114] For the test material with a plate thickness of 0.2 mm, a test was conducted by punching a 5 mm × 5 mm square test piece using a die. The gap was set at two levels of 5% and 10% relative to the plate thickness. Among the four cuts (end faces) formed on the square test piece, two opposite cuts were punched perpendicular to the rolling direction. Figure 1 The shape of the cut of the punched test piece is schematically shown in the figure. The size of the burr is exaggerated. For the cut parallel to the rolling direction of the test piece, the surface height when the cut is viewed from the normal direction (in this case, the direction perpendicular to the rolling direction and the plate thickness direction) using a laser microscope is measured online in the entire plate thickness direction (punching axis direction) to create a profile of surface unevenness. From the profile, determine Figure 1 The length of the shear surface represented by symbol A in the figure is used to find the ratio of the shear surface to the fracture surface. Figure 1 The length including the burr portion indicated by symbol B is regarded as the length of the fracture surface, and the "shear surface ratio" is calculated according to the following formula (2). In this punching test, the height of the burr is usually less than 1 μm, so including the burr in the length of the fracture surface does not hinder the evaluation of punchability.
[0115] Shear surface ratio (%) = 100 × A / (A+B)…(2)
[0116] The measurement is performed at 10 locations in the cut (end face) parallel to the rolling direction of the test piece, and the shear surface ratio is calculated at each location according to formula (2), and their arithmetic mean is used as the shear surface ratio of the test material. In this test, when the shear surface ratio under the gap of 5% becomes less than 40%, and the shear surface ratio under the gap of 10% becomes less than 30%, it can be judged that a significant improvement in stamping performance is confirmed compared with the conventional general Cu-[Ni, Co]-Si copper alloy sheet. Therefore, the shear surface ratio under the gap of 5% is less than 40%, and the shear surface ratio under the gap of 10% is less than 30%.
[0117] (Fatigue properties)
[0118] A test piece with a width of 3 mm and a length of 20 mm, with the width direction being the rolling direction (LD) and the longitudinal direction being the rolling perpendicular direction (TD), was cut out from the test material, and a bidirectional vibration fatigue test using the cantilever resonance method was carried out with a load stress of 300 MPa using a fatigue testing device (manufactured by Japan Technoplastics Co., Ltd., RF-RT). During the test, the change in the resonant frequency was monitored, and the number of cycles at the moment when the value of the initial resonant frequency was 98% was taken as the fatigue limit of the test piece. This operation was performed on 5 test pieces made from 1 test material, and the average value of their fatigue limits was taken as the fatigue limit of the test material. The fatigue limit was set to 10 6 The above cycles are judged as qualified.
[0119] The above results are shown in Tables 1 to 4.
[0120]
Table 1
[0121]
[0122]
Table 2
[0123] Table 2
[0124]
[0125]
Table 3
[0126] Table 3
[0127]
[0128] Underline: outside the scope of the present invention
[0129]
Table 4
[0130] Table 4
[0131]
[0132] Underline: outside the scope of the present invention
[0133] For the test materials of the present invention example containing a specified amount of S, the number density of S-containing particles with a long diameter of 2.0 μm or more and less than 5.0 μm, and the number density of S-containing particles with a long diameter of 5.0 μm or more are controlled within the above-mentioned appropriate range, a significant improvement in stamping properties is obtained while maintaining good bending workability, and good fatigue properties can be achieved at a medium strength level (tensile strength in the rolling direction is 500 MPa or more and less than 900 MPa). The electrical conductivity is also 40% IACS or more, which is good.
[0134] In contrast, in No. 41 as a comparative example, since the S content was high, the number density of S-containing phase particles having a major diameter of 5.0 μm or more could not be sufficiently reduced, and the bending workability and fatigue properties were poor.
[0135] In No. 42, 43, 44, 45, 46, 51, 52, 53, 54, and 55, the number density of S-containing phase particles with a major diameter of 2.0 μm or more and less than 5.0 μm is reduced due to the low S content, and the improvement of punchability is insufficient. In particular, in No. 45 and 53, the total content of Ni and Co is high, so the strength level is improved, but the bending workability and conductivity are also poor.
[0136] In No. 47, since the cooling rate during casting was low, the number density of S-phase-containing grains having a major diameter of 5.0 μm or more increased, and the bending workability and fatigue properties were poor.
[0137] In No. 48, since the molten metal temperature during casting was low, S was not sufficiently dissolved, resulting in an increase in the number density of S-containing phase grains having a major diameter of 5.0 μm or more, and poor bending workability and fatigue properties.
[0138] In No. 49, since the total content of Ni and Co is small, precipitation strengthening becomes insufficient, the strength level is low, and the fatigue characteristics are also poor.
[0139] In No. 50, since the Si content is small, precipitation strengthening becomes insufficient, the strength level is low, and the fatigue characteristics are also poor.
Claims
1. A copper alloy plate having the following chemical composition, including: Expressed in mass %, the total of Ni and Co: 1.00-3.60%, Si: 0.20-2.00%, S: 0.005-0.10%, Ag: 0-1.00%, Al: 0-3.00%, B: 0-0.50%, Cr: 0-1.00%, Fe: 0-3.00%, Mg: 0-1.50%, Mn: 0-1.50%, P: 0-0.50%, Sn: 0-3.00%, Ti: 0-1.00%, Zn: 0-3.00%, Zr: 0-1.00%, the balance is Cu and unavoidable impurities, wherein the number density of S-containing particles having a major diameter of 2.0 μm or more and less than 5.0 μm is 50 particles / mm 2 The number density of S-containing particles with a major diameter of 5.0 μm or more is 50 particles / mm 2 the following.
2. The copper alloy sheet material according to claim 1, wherein: The total content of Ag, Al, B, Cr, Fe, Mg, Mn, P, Sn, Ti, Zn, and Zr is 4.00 mass% or less.
3. The copper alloy sheet material according to claim 1, wherein: The Ni content is 0.80 to 3.50 mass %.
4. The copper alloy sheet material according to claim 1, wherein: The tensile strength in the rolling direction is 500 MPa or more and less than 900 MPa.
5. The copper alloy sheet material according to claim 1, wherein: The electrical conductivity is 40% IACS or more.
6. The copper alloy sheet material according to claim 1, wherein: The ratio MBR / t of the minimum bending radius MBR and the plate thickness t at which cracks are not generated in a 90° W bending test under BW in accordance with the technical standard JCBAT307:2007 of the Japan Copper and Copper Industry Association is 2.5 or less.
7. The copper alloy sheet material according to claim 1, wherein: In a bidirectional vibration fatigue test using a cantilever resonance method with a test piece whose longitudinal direction is perpendicular to the rolling direction, the fatigue limit at a load stress of 300 MPa is 10 6 Loop above.
8. A current-carrying component using the copper alloy sheet material according to any one of claims 1 to 7 as a material.
9. A heat dissipating component using the copper alloy sheet material according to any one of claims 1 to 7 as a material.
Citation Information
Patent Citations
Copper-alloy material
JP2011117034A
Cu-Ni-Si-Co COPPER ALLOY FOR ELECTRONIC MATERIAL AND PROCESS FOR PRODUCING SAME
JP2011214088A
Copper alloy, and method of manufacturing the same
JP2012224922A
Cu-Ni-Si-BASED ALLOY AND METHOD FOR PRODUCING THE SAME
JP2013095977A
Method for manufacturing copper alloy sheet material
JP2015187308A